MODEL OF ISLAMIC PHILANTROPHIC FUND MANAGEMENT IN INDONESIAN SHARIA FINANCIAL INSTITUTIONS (LKS) - Nurul Qomariyah (Faculty of Islamic Economics and Business, 2022)
Introduction : The purpose of this study is to find out the management model of zakat, infaq and alms and the distribution process for economic empowerment carried out by Islamic Financial Institutions with a case study at BMT Marhamah Indonesia Methods :This research uses a type of qualitative research with a descriptive method. The data used in this study is a type of primary data obtained directly from interviews and secondary data originating from BMT Marhamah Indonesia Result :research shows that the management model carried out by Baitul Mal BMT Marhamah is collection applying fundrising logic, distribution in a consumptive and productive form, assistance in the form of business training and controlling capital development. Empowerment programs are able to improve the economy and build community mentality.